2018
DOI: 10.1080/19396368.2018.1482383
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a complex population of chromatin-associated proteins in the European sea bass (Dicentrarchus labrax) sperm

Abstract: A very common conception about the function of the spermatozoon is that its unique role is to transmit the paternal genome to the next generation. Most of the sperm genome is known to be condensed in many species by protamines, which are small and extremely positively charged proteins (50-70% arginine) with the functions of streamlining the sperm cell and protecting its DNA. However, more recently, it has been shown in mammals that 2-10% of its mature sperm chromatin is also associated to a complex population … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 158 publications
(210 reference statements)
0
8
0
Order By: Relevance
“…However, they could also be regarded as a sort of 'essential epigenetic marks', as defined elsewhere [37], with respect to dynamic CpGs, which when properly combined can help to predict phenotypic sex (see below). Also, in a recent study in the European sea bass we have shown that the sperm, in addition to its DNA, carries a complex population of chromatin-associated proteins [75], providing further possibilities for the epigenetic transmission of information across generations.…”
Section: Discussionmentioning
confidence: 94%
“…However, they could also be regarded as a sort of 'essential epigenetic marks', as defined elsewhere [37], with respect to dynamic CpGs, which when properly combined can help to predict phenotypic sex (see below). Also, in a recent study in the European sea bass we have shown that the sperm, in addition to its DNA, carries a complex population of chromatin-associated proteins [75], providing further possibilities for the epigenetic transmission of information across generations.…”
Section: Discussionmentioning
confidence: 94%
“…The European sea bass has become one of the most studied species in sh epigenetics [77][78][79][80][81][82][83][84]. Because of the availability of its genome and the development of selection programs, efforts should be dedicated to further explore its epigenomic landscape regarding the stress response, especially in an aquaculture context.…”
Section: Resultsmentioning
confidence: 99%
“…It has been extensively studied over the last three decades, for both natural and farmed populations (reviewed in [75]). This includes the sequencing of its genome [76] and an increasing number of epigenetic studies [77][78][79][80][81][82][83][84]. The stress response of European sea bass remains evaluated using blood parameters that have been shown to re ect multiple components of its stress response [16,85], despite authors have proposed alternatives [86,87].…”
Section: Introductionmentioning
confidence: 99%
“…Several collaborative projects were developed and published with Gordon in subsequent years after Rafael had completed his postdoctoral training and become established as an independent scientist at the University of Barcelona (54,55). The appreciation for the reproductive biology experimental model from Gordon, as a major mentor, determined the primary focus of Rafael's subsequent scientific career, with a substantial imprint in the study of the protamines, chromatin structure and the 'omic' composition in spermatogenesis (de Yebra et al 1993;Oliva 2006;Jodar et al 2011;Castillo et al 2014Castillo et al , 2018Barrachina et al 2018;Soler-Ventura et al 2019).…”
Section: The University Of Calgary (1974-1994)mentioning
confidence: 99%